PEMANFAATAN RADAR DAN PENGAMBILAN KEPUTUSAN NAVIGASI DI ALUR PELAYARAN (TSS): IMPLIKASINYA TERHADAP PENCEGAHAN TUBRUKAN PADA OPERASI KAPAL PENYEBRANGAN - Abi Siswanto Dg Malewa; Subehana Rachman; Andi Anna Mutmainnah (STKIP Subang, 2026)
This study aims to analyze the utilization of radar and navigation decision-making in Traffic Separation Schemes (TSS) shipping lanes and its implications for collision prevention on ferry operations of KMP. Portlink. The research method used is descriptive qualitative with an ex post facto approach. Data were obtained through direct observation, in-depth interviews with the Captain and deck officers, and documentation studies during 12 months of sea practice. The data analysis technique uses the Miles and Huberman interactive model. The results indicate that radar utilization on KMP. Portlink is still not optimal, characterized by damage to the magnetron and radar power supply causing navigation disruptions in the Sunda Strait TSS area. The main causal factors include the lack of watch officers' understanding of radar features (Parallel Index, EBL, VRM, CPA/TCPA), weak routine maintenance procedures on radar components, and limited standard operating procedures in handling disruptions. The impacts of these obstacles include collision risks, operational delays, and potential navigation safety hazards. Efforts to overcome these obstacles include enhancing officer supervision, conducting toolbox meetings, implementing strict SOPs for radar use and maintenance, crew competency training, and routine component maintenance according to the manual book. Proper implementation of radar usage procedures and navigation decision-making is expected to prevent collision hazards and maintain compliance with COLREG 1972 and SOLAS Chapter V standards.